Penguatan Dakwah Digital PDM Kota Surakarta Melalui Website Muhammadiyahsolo.com - Agus Triyono; Suranto Suranto; Kuswaji Dwi Priyono (Journal of Dedicators Community, 2020)
Technological developments significantly  makes da'wah evolve from offline to online using internet media. By the collaboration of da'wah and the internet, the values of Muhammadiyah Da'wah will be more easily dispersed and absorbed by the audience. The focus in this activity is to build a website system that becomes the means of digital da'wah, especially in the Distrcit Commitee of Surakarta. The method of implementation in this activity is FGD, website building, socialization, training and maintenance. In each activity, attended by representatives of Ortom, assembly, and Charity Enterprises Muhammadiyah (AUM). From the dedication activities that have been implemented can be concluded that the program has been running in accordance with the results of discussions between partners and executor. From the level of activity of each trainees in submitting the news is pretty good. This can be seen from the data contained in the website The significant increase in the number of articles containing information and articles uploaded at muhammadiyahsolo.com. Data from May – December 2019 shows an increase in the number of articles or news posted in total there are 142 manuscripts in a variety of categories : News, Tajdid, business charity schools and others with the number of view pages About 1500